Depressive response in children with insulin-dependent diabetes - Laghouat schools as a model - - CHLAOUCHI, Oum ennoune; ARAR, Samia (Social Sciences Journal)
The study in hands aims to identify the depressive responsiveness of type 1 diabetic children, through recognizing their physical, psychological and neurological environment; in addition to their behavioral and Gnostic environment. Therefore, the researcher attentively selected a sample of 04 children to do a legalized interview with their teachers including a T.A.T test. As a result of the study, children have a depressive responsiveness embodied in physical, psychological, neurological, Gnostic and behavioral effects.